PENGEMBANGAN MODEL BELAJAR BERMUTU YANG ADAPTIF UNTUK MENINGKATKAN KINERJA GURU SEKOLAH DASAR TERPENCIL - Dodo Sutardi (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2016)
Abstract: The purpose of this research is to produce excellent learning models which are adaptable and examine its effectiveness. The learning model is directed to increase teachers’ performance in remote elementary schools. This research used two approaches which are; qualitative descriptive, and experiment with non-equivalent model control group design at four Elementary School within remote area in Seluma Regency, Bengkulu Province. The research results showed that (1)the Excellent Learning Model (PTK based teaching) adjusted with the limited teachers’ academic qualification, learning infrastructure, the minimum training experience, low internal motivation, and (2) Adaptable Excellent learning model is more effective in increasing teachers’ performance in remote area Elementary School. Abstrak: Penelitian ini bertujuan (1) menghasilkan model belajar BERMUTU yang adaptif, dan (2) menguji keefektifan model belajar Bermutu yang adaptif dalam meningkatkan kinerja guru SD terpencil. Penelitian dilakukan pada 4 SD terpencil di Kabupaten Seluma Provinsi Bengkulu. Penelitian ini menggunakan dua pendekatan yaitu; deskriptif kualitatif, dan eksperimen dengan model noequivalent control group design. Hasil penelitian: (1) Model belajar Bermutu (pembelajaran berbasis PTK) disesuaikan dengan keterbatasan kualifikasi akademik guru, sarana prasarana pembelajaran, minimnya pengalaman pelatihan, motivasi internal yang rendah, dan (2) Model pembelajaran Bermutu yang adaptif lebih efektif dalam meningkatkan kinerja guru SD terpencil.